Impact of Tourniquet Use on Systemic Inflammatory Parameters, Functional Physical Recovery, and Cardiovascular Outcomes of Patients Undergoing Knee Arthroplasty: A Case-Control Study - Bressi, Edoardo; Longo, Umile Giuseppe; Mangiacapra, Fabio; Candela, Vincenzo; Berton, Alessandra; Salvatore, Giuseppe; Capuano, Marialessia; Proietti, Riccardo; Denaro, Vincenzo (The Journal of Knee Surgery, 2020)
The benefits of tourniquet use during orthopaedic surgery are controversial. We aim to investigate its effects on systemic inflammation, functional physical recovery, and cardiovascular complications of patients undergoing knee arthroplasty. We enrolled 129 consecutive patients (57 treated with tourniquet vs. 72 in the control group) undergoing total unilateral knee arthroplasty, followed by inpatient rehabilitation protocol at our institution. Blood samples were drawn in all patients at baseline and within 24 hours after surgery for complete blood cell count assessment. Neutrophil-to-lymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR) were calculated as the ratio between the absolute number of neutrophil and platelets over the absolute number of lymphocytes, respectively. The numeric rating scale (NRS; 0–10) assessed the current pain, day after the surgery. All subjects underwent physical functional evaluation measured by the modified Barthel's index (MBI) at the end of the rehabilitation. We also recorded the incidence of major bleeding, typical angina, and occurrence of atrial fibrillation after surgery. In the overall population, a significant postprocedural increase in NLR and PLR was observed (p < 0.001). Baseline NLR and PLR were similar in patients with and without tourniquet (1.5 ± 0.8 vs. 1.95 ± 1.2, p = 0.081; 120 ± 42 vs. 131 ± 55, p = 0.240); however, patients treated with tourniquet showed significantly lower NLR at 24 hours (6.1 ± 3.6 vs. 8.1 ± 5.7, p = 0.043). NRS scores were significantly higher in the tourniquet group without compromising functional and physical recovery whereas no significant differences were appreciated in MBI scores between the two groups. Moreover, the rates of postoperative atrial fibrillation (1 [2%] vs. 9 [12%], p = 0.042) and major bleeding (2 [4%] vs. 11 [15%], p = 0.038) were significantly lower in the tourniquet group. Tourniquet seems a useful tool which is able to mitigate the inflammatory activation and prevent the occurrence of atrial fibrillation and major bleeding without altering functional physical recovery of patients undergoing total knee arthroplasty.
Keywords: total knee arthroplasty; neutrophil-to-lymphocyte ratio; platelet-to-lymphocyte ratio; pain activity; cardiovascular; major bleedings; tourniquet